Penanggulangan Keadaan Darurat Ancaman Covid-19 dalam Sudut Pandang Tata Negara - Dahoklory, Madaskolay Viktoris (Jurnal Keamanan Nasional, 2020)
Since being declared an international pandemic by WHO, the plague of the COVID-19 disease has spread to all sectors of good community life, public health to the national economy, until finally, the President establishes national status in a state of public health emergency. The purpose of writing is to understand the concept of an emergency, policies that can be taken by the Government during an emergency, and provide a recommendation for the emergency situation. The research method is normative by using the statutory approach and conceptual approach to analyze the problem qualitatively. Research results show that, when the state of an emergency has been determined by the President, then any policy may be carried out by the state to cope with the emergency. For example, raising BPJS fees, delaying payment of PNS salaries, and so on. Except, the policy that cannot be carried out by the state during an emergency situation is to reduce or deviate human rights guaranteed in Article 28I of the 1945 Constitution or often referred to as “non derogable rights”. Therefore, the author recommends that the Government implement a “new normal life” in order to maintain a stable balance between public health and the national economy.